Proinflammatory status of oral fluid in COVID-19 - I. A. Borodina; O. A. Gusyakova; I. A. Selezneva; F. N. Gilmiyarova; A. A. Ereshchenko; O. A. Baldina; N. A. Kolotyeva; O. V. Borisova (Медицинская иммунология, 2021)
At present, a search for promising ways to diagnose infection caused by SARS-CoV-2 is quite relevant. Oral fluid is not commonly used for assessment of COVID-19 risk. Its molecular profile reflects both local state of the oral cavity, and individual organs and systems, thus suggesting a reliable diagnostic platform. Systemic inflammatory response is known to play a crucial role in development of the coronavirus infection; the “cytokine storm” determines severity of the disease. The saliva-based diagnostics of clinical course in COVID-19 patients includes determination of IL-6, IL-8, C-reactive protein in oral fluid, in order to assess severity of the inflammatory process. The present study was carried out at the Department of Fundamental and Clinical Biochemistry with Laboratory Diagnostics, and Department of Pediatric Infections at the Samara State Medical University. The study involved 122 persons: 67 clinically healthy individuals comprised the control group, and the group of comparison included 55 inpatients with moderate or severe coronavirus infection (COVID-19) caused by SARS-CoV-2 virus as confirmed by PCR and/or ELISA testing. Development of the disease was accompanied by drastically increased contents of IL-6 and IL-8 in oral fluid of the patients relative to the indexes in healthy persons, i.e., several-fold for IL-6 (+ 650%) and even higher elevation of IL-8 levels (+ 26513%), as well as a 2-fold increase of C-reactive protein (+115%). When comparing the immune indexes of oral fluid in presence versus absence of respiratory insufficiency, a significant difference was found for salivary IL-6 (+173%) in the patients with grade 1-2 respiratory insufficiency as compared with patients free of respiratory disorders. Determination of these proinflammatory markers in patients with COVID-19 is of important prognostic significance when assessing development of the disease and its severity. Direct detection of their content in the oral fluid makes this method relevant, and potentially demanded for the outpatient diagnostics, being highly important during pandemics of coronavirus infection and limited medical resources. Examination of oral fluid at the pre-hospital stage is a resource-saving technology, since it does not require additional medical staff to take biomaterial, is non-invasive to the patient, and suggesting a wide range of research items, it can resolve a number of diagnostic issues, e.c., presence of specific genetic material or antibodies to SARS-CoV-2, severity of the inflammatory process and the risk of respiratory failure in the patient.